If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -29y = -23 Solving 5x + -29y = -23 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '29y' to each side of the equation. 5x + -29y + 29y = -23 + 29y Combine like terms: -29y + 29y = 0 5x + 0 = -23 + 29y 5x = -23 + 29y Divide each side by '5'. x = -4.6 + 5.8y Simplifying x = -4.6 + 5.8y
| .7(x+5)+.4(x+25)=30 | | -3(-6n+3)-7n=-86 | | .1428(x+7)+.035(x-28)=x+23 | | x^2+2=102 | | 5b-5-12b-8= | | d(x)=2x-4 | | X=180+0.6(60+0.2x) | | Log(16+2x)=log(x^2-4x) | | X=180+0.6+(60+0.2) | | x^2-39x+376=0 | | X=180+0.6y | | 5x+1=-25-2x | | 80x^4+72x^3-47x^2-15x=0 | | 3t-15=2+10 | | (2+z)(4z-1)=0 | | 3cosx*sinx=1 | | 4x-18=3x+5 | | 6(t-2)+4t=5(2t+4)-9 | | (s)(-3st)(-1/3) | | y+115+65= | | 3x+6=6x+20 | | logbase(2x+6)144=2 | | -2(3x+2)=-48 | | Sin^2x-2cosx-2=0 | | 5(6x-4)=34x | | 10-2w=6 | | 2u+2=5p-10 | | 1+-2g=5 | | 4/15-3/15 | | 13a-1=90 | | -(6y+3)-(-5-4)=-7 | | P=4c-20+2c |